LITERATURE REVIEW: IMPLEMENTASI HILIRISASI NIKEL DI INDONESIA - Natus, Angelique Salsabillah Yumna Patricia; Rohman, Faris Sahrur; Zhahral, Arsyilia; Sumarya, Erdin Handika; Widiyarta, Agus (Al-Amien Prenduan University, Sumenep, 2024)
Nickel downstreaming is one of the government's policy programs in developing the mineral mining sector which is currently being developed to implement it. At the beginning of 2024, nickel downstreaming became an interesting topic discussed among the public, because it was mentioned in the vice presidential debate. This article analyzes how nickel downstreaming is implemented using Edward III's theory. The research method used is Systematic Literature Review (SLR). The data used in the research comes from the Google Scholar, ScienceDirect, ResearchGate and FreeFullPdf publication databases with the keywords nickel downstream, Indonesian nickel downstream, mineral downstream, Indonesian mineral downstream. Based on the results of the analysis, the nickel downstream program in Indonesia still requires investment to build a smelter, implement regulations that pay attention to the environment in mining activities, prioritize migrant workers over foreign workers in mining activities, study the manufacture of nickel to become semi-finished goods and should even be able to study the manufacture of electric batteries so that it can do independent production of finished goods.